Comparison of Efficacy and Safety of Talc to Povidone-Iodine Pleurodesis in Malignant Pleural Effusion: A Systematic Review and Meta-Analysis - Divya Balan; Tejaswini Baral; Mohan K. Manu; Aswini Kumar Mohapatra; Sonal Sekhar Miraj (Indian Journal of Medical and Paediatric Oncology)
Malignant pleural effusion (MPE) poses a substantial clinical challenge, necessitating effective interventions. Pleurodesis, commonly employed in MPE management, involves inducing pleural symphysis to prevent fluid accumulation. Talc and povidone-iodine have emerged as prominent agents for pleurodesis, each with its unique characteristics and considerations. This systematic review and meta-analysis aimed to compare the efficacy and safety of talc powder pleurodesis (TPP) and povidone-iodine pleurodesis (PIP) in the management of MPE. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a systematic review registered in PROSPERO (CRD42023470930). Randomized controlled trials (RCTs) with TPP and PIP arms for MPE were included. The information sources included electronic bibliographic databases such as PubMed, Scopus, Web of Science, Cochrane, and Embase from inception to November 2023. The Cochrane risk of bias tool was used for the critical appraisal. A meta-analysis using RevMan 5.3 compared outcomes. Out of 105 identified records, 3 RCTs were included in our review. Our review findings revealed a higher success rate for TPP. However, variability existed, with one study indicating better success rates in PIP groups. Adverse events were reported less frequently in the PIP group, suggesting a potentially superior safety profile. TPP showed higher overall success in comparison to PIP, emphasizing the need for cautious clinical decision-making given variability. The potential superior safety profile of povidone-iodine underscores the importance of context-specific choices, considering patient preferences and resource constraints in selecting pleurodesis interventions for MPE management.